The Regulation Models in Financial Markets: The Message of the Encyclical (Cultura Económica, 2019)
The author analyzes the global financial crisis in the light of the new Encyclical. From her point of view, globalization has changed the ability of States to regulate financial activities and therefore requires new ways of re-channeling the financial system to avoid a new crisis.To this end, the author discusses the construction of institutions for the financial system, proposes alternative ways to overcome the model of anonymous and mechanical markets of recent years and suggests educational interventions.
Keywords: crisis; finance; regulation; institutions; education